Morphological and genomic responses to hurricanes arise and persist during a biological invasion - Jason J. Kolbe; Sean T. Giery; Ansley S. Petherick; Jonathan B. Losos; Dan G. Bock (Proceedings of the National Academy of Sciences, 2025)
Hurricanes can be a source of strong, episodic natural selection, especially for coastal and island populations. In Anolis lizards, selection favors morphological traits that enhance clinging performance under hurricane-force winds. However, we know little about the longer-term persistence of morphological and genomic responses to these pulse-like events. To address this limitation, we capitalized on the well-documented history of hurricanes and spread of the invasive brown anole lizard, Anolis sagrei , over the past 130 y in the southeastern United States. We used 30 sites with estimates of the number of hurricanes experienced since population establishment. We found that hurricane frequency is consistently related to morphological trait values that increase clinging performance—longer limbs and larger toepads. In contrast, traits with no known connection to clinging ability were not related to hurricane frequency. Our genomic results show that despite a complex genetic architecture for most traits, populations retain a signature of hurricane-mediated selection, with several loci being strongly associated with both hurricane frequency and longer limbs. Further, we found that hurricanes are a more persistent driver of among-population genomic differentiation than other environmental variables. These results solidify hurricanes as a major force shaping morphological and genomic variation in Anolis lizards. They also highlight how the evolutionary trajectories of populations will likely be altered as climate change modifies historical patterns of natural selection, such as those involving extreme weather events.